Convergence of an impulsive storage process with jump switchings - Samoilenko, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We investigate an impulsive storage process switched by a jump process. The switching process is, in turn, averaged. We prove the weak convergence of the storage process in the scheme of series where a small parameter ε tends to zero.